An Economic and sustainable planning of Bhasan Char as an Exclusive tourism spot with off-grid SMART Green Energy System - Nasrin, Taskina; Uzzal, Mohammad Mohiuddin (AIUB Journal of Science and Engineering (AJSE), 2020)
Bhasan char is a coastal island at Hatiya Upzilla of Noakhali District. It is a single char which has been uncovered from the Bay of Bengal a few years back. An emergency humanitarian project implemented by the Bangladesh government at this coastal island “Bhasan Char”, from September 2017, to temporarily rehabilitate a portion of incoming Rohingya refugees before they can repatriate to their homeland, Myanmar. Under this project, Government of Bangladesh (GoB) carried out land development, construction of embankment as well as other infrastructures. Upon repatriation of Rohingya's to Myanmar, we can use the developed land & surroundings as exclusive tourist zone. This paper is an outline to establish Bhasan Char as an exclusive tourist spot and a feasibility analysis of an off-grid hybrid energy generation system for this proposed tourism spot. Here, we had conducted a hypothetical zonal design, energy estimation, off-grid energy distribution, energy generation and a sustainable tariff plan for this exclusive zone in modular basis.